Japan considered from the hypothesis of farmer/language spread - Elisabeth de Boer; Melinda A. Yang; Aileen Kawagoe; Gina L. Barnes (Evolutionary Human Sciences, 2020)
Formally, the Farming/Language Dispersal hypothesis as applied to Japan relates to the introduction of agriculture and spread of the Japanese language (between ca. 500 BC–AD 800). We review current data from genetics, archaeology, and linguistics in relation to this hypothesis. However, evidence bases for these disciplines are drawn from different periods. Genetic data have primarily been sampled from present-day Japanese and prehistoric Jōmon peoples (14,000–300 BC), preceding the introduction of rice agriculture. The best archaeological evidence for agriculture comes from western Japan during the Yayoi period (ca. 900 BC–AD 250), but little is known about northeastern Japan, which is a focal point here. And despite considerable hypothesizing about prehistoric language, the spread of historic languages/ dialects through the islands is more accessible but difficult to relate to prehistory. Though the lack of Yayoi skeletal material available for DNA analysis greatly inhibits direct study of how the pre-agricultural Jōmon peoples interacted with rice agriculturalists, our review of Jōmon genetics sets the stage for further research into their relationships. Modern linguistic research plays an unexpected role in bringing Izumo (Shimane Prefecture) and the Japan Sea coast into consideration in the populating of northeastern Honshu by agriculturalists beyond the Kantō region.